The use of carbon monoxide breath test to detect the effect of iron overload on erythrocyte lifespan in MDS - Zhang, Yao; Qian, Yan; Song, Lu-xi; Xiao, Chao; Chang, Chun-kang (Frontiers in Oncology, 2022)
Objective: To investigate the effect of iron overload (IO) on red blood cell(RBC) lifespan in MDS patients with the use of carbon monoxide breath test. Methods: The red cell lifespan of 93 patients with myelodysplastic syndrome (MDS) and 22 healthy volunteers in the control group were measured by alveolar gas carbon monoxide (CO) assay, with the detection of liver iron concentration, iron metabolism index, erythropoietin (EPO) concentration, peripheral blood inflammatory cytokines, etc. The MDS patients were divided into the severe IO group, mild IO group and non IO group according to liver iron concentration. The effect of IO on RBC lifespan was analyzed in MDS patients. Results: The RBC lifespan of MDS patients in the severe IO group was significantly lower than that in the mild IO group (p<0.05), while the RBC life span in the mild IO group was significantly lower than that in the non IO group (p<0.05). The expression of inflammatory cytokines in the severe IO group was significantly higher than that of the mild and non IO groups. After receiving iron removal treatment(ICT), the expression of inflammatory cytokines was decreased significantly, and the RBC lifespan was significantly prolonged (p<0.05).Besides, liver iron concentration was significantly positively correlated with EPO concentration, while EPO concentration was significantly negatively correlated with RBC lifespan, especially in the MDS-RS subgroup. The RBC lifespan in the EPO>1000 group was significantly lower than that in the EPO<1000 group. Conclusion: IO can shorten RBC lifespan in MDS patients, which may be result from the increase of endogenous EPO and the over-expression of inflammatory cytokines. After ICT, the ineffective hematopoiesis caused by increased EPO and the decrease of inflammatory cytokine may significantly prolong the RBC lifespan in MDS patients.